Rethinking the Daoist Concept of Nature. Issue 3 (25th June 2018) - Chai, David
Abstract: Recent years have seen an increased turning to the "wisdom of the East" when addressing issues on the environment. The risk of misappropriating its tenets in order to make them conform to the Western system is extremely high however. This paper will lay bare the early texts of Daoism so as to disprove claims that Nature is mystical, antithetical to technology, and subservient to human consciousness. It shall argue that Nature not only arises from a non‐anthropocentric source in Dao but that this arising takes place across three levels of reality: Dao's mystery, the cosmogony of the One‐and‐Many, and the fourfold comprised of Dao, Heaven, Earth, and man. The result is a vision of Nature no longer bound to a singular actuality but one whose presence is felt across an endless range of possibilities as the substantive realization of Dao.